Desensitization Using Bortezomib and High-dose Immunoglobulin Increases Rate of Deceased Donor Kidney Transplantation - Jeong, Jong Cheol (Medicine (Baltimore), 2016)
Combination therapy of intravenous immunoglobulin (IVIG) and rituximab showed a good transplant rate in highly sensitized wait-listed patients for deceased donor kidney transplantation (DDKT), but carried the risk of antibody-mediated rejection. The authors investigated the impact of a new combination therapy of bortezomib, IVIG, and rituximab on transplantation rate. This study was a prospective, open-labeled clinical trial. The desensitization regimen consisted of 2 doses of IVIG (2 g/kg), a single dose of rituximab (375 mg/m(2)), and 4 doses of bortezomib (1.3 mg/m(2)). The transplant rate was analyzed. Anti-Human leukocyte antigen (HLA) DRB antibodies were determined by a Luminex solid-phase bead assay at baseline and after 2, 3, and 6 months in the desensitized patients. There were 19 highly sensitized patients who received desensitization and 17 patients in the control group. Baseline values of class I and II panel reactive antibody (%, peak mean fluorescence intensity) were 83 ± 16.0 (14952 ± 5820) and 63 ± 36.0 (10321 ± 7421), respectively. Deceased donor kidney transplantation was successfully performed in 8 patients (42.1%) in the desensitization group versus 4 (23.5%) in the control group. Multivariate time-varying covariate Cox regression analysis showed that desensitization increased the probability of DDKT (hazard ratio, 46.895; 95% confidence interval, 3.468–634.132; P = 0.004). Desensitization decreased mean fluorescence intensity values of class I panel reactive antibody by 15.5% (20.8%) at 2 months. In addition, a liberal mismatch strategy in post hoc analysis increased the benefit of desensitization in donor-specific antibody reduction. Desensitization was well tolerated, and acute rejection occurred only in the control group. In conclusion, a desensitization protocol using bortezomib, high-dose IVIG, and rituximab increased the DDKT rate in highly sensitized, wait-listed patients.